Local History Learning Based on The Struggle of The Mobrig Troops In Yogyakarta to Increase Students' Historical Awareness - Arif Krisna Sudarmaji; Akhmad Arif Musadad; Hieronymus Purwanta (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
An important problem that is often neglected in the study of Indonesian history today is the lack of discussion of the local historical context. History teachers are often fixated on the material presented in lks and course textbooks. Like a lack of attention to historical events that have happened around. For this reason, it is necessary to introduce local historical material to increase students' historical awareness, such as material on the local history of the struggle of the Mobrig troops in Yogyakarta. The research methodology used to increase students' historical awareness is descriptive qualitative. This method is carried out by distributing a questionnaire containing questions about historical awareness. The findings obtained at SMK N 1 Pengasih Kulon Progo show that the historical awareness of students has increased, this can be seen after the researcher gave a questionnaire before and after providing material on the Fight for Mobrig Troops in Yogyakarta. Based on the results of the study, it can be concluded that by providing local history material to students at SMK N 1 Pengasih Kulon Progo it can increase students' historical awareness.